PRELIMINARY DRAFT - ETS PROJECT - WK 19840524 (Tufts Archival Research Center, 2007)
Draft; Tobacco Institute (TI) report on strategies to combat the anti-smoking advocacy environmental tobacco smoke (ETS) campaign. Breaks down campaign into annoyance attack, economic attack, and scientific attack. Identifies the ETS argument as a major threat and as the strongest base for public anti-smoking support. Asserts need to inspire and support competent ETS research, advocate social politeness , and do further research into the economic effects of ETS.